Pharmacokinetics, pharmacodynamics and safety of 15 mg-tolvaptan administered orally for 7 consecutive days to Chinese patients with child-Pugh B cirrhosis - Liu, Hongzhong; Wang, Yongfeng; Liu, Tao; Chen, Yingxuan; Zheng, Xin; Liu, Ming; Zhao, Qian; Zeng, Minde; Jiang, Ji; Mao, Yimin; Hu, Pei (Frontiers in Pharmacology, 2024)
Background: Tolvaptan, a selective vasopressin V2-receptor antagonist, can elicit a diuretic effect without significant electrolyte loss. The aims were to evaluate multiple-dose pharmacokinetics, pharmacodynamics and safety of daily administration of 15 mg tolvaptan in Chinese adult patients with confirmed Child-Pugh Class B cirrhosis accompanied by ascites. Methods: This was an open-label, single-center, single- and multiple-dose study. All patients received a daily 15 mg dose of tolvaptan for 7 consecutive days. The plasma concentrations of tolvaptan and its two metabolites (DM-4103, DM-4107) were measured using high-performance liquid chromatography with tandem mass spectrometry (HPLC-MS/MS). In addition, various pharmacokinetics parameters were calculated. The pharmacodynamic outcomes evaluated changes in serum sodium and potassium concentrations, daily urine volume, daily water consumption, fluid balance and body weight. Safety profiles, including the incidence of treatment-emergent adverse events (TEAEs), were carefully recorded. Results: Eleven patients with Child-Pugh B cirrhosis were eventually enrolled in the study. Plasma concentrations of tolvaptan and DM-4107 reached steady-states after 7 days of consecutive oral administration. No accumulation of tolvaptan or DM-4107 was found, but DM-4103 accumulated 18.2-fold after multiple-dosing. The daily urine volume and daily water consumption were statistically significantly increased after administration of tolvaptan from Day 1 to Day 7 (all P < 0.05), accompanied by an increased serum sodium concentration. Of 11 patients, 9 (81.8%) reported 20 TEAEs, with the majority being mild to moderate in severity. The most commonly occurring TEAEs were thirst (45.5%), pollakiuria (36.4%) and dry mouth (27.3%). Conclusions: Tolvaptan at a daily dose of 15 mg had a diuretic effect but did not increase serum sodium excretion or lead to tolvaptan accumulation. It is therefore can be safely used for short-term treatment of Chinese adult patients with confirmed Child-Pugh B cirrhosis. Trial registration: NCT01359462